2021
DOI: 10.1177/10775463211035903
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to inertial damper design to control base displacement in isolated buildings

Abstract: A novel design procedure for tuned mass dampers in isolated structures is presented. The proposed optimization method is specifically developed to control base displacements or to solve the large isolator displacement problem in this type of structures under earthquakes. Therefore, it is based on a displacement transmissibility function, T, a particular case of the general transmissibility concept, which comes from Vibration Isolation. Three contributions are application of new seismic displacement narrowbandn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It can also be argued that the predominant period obtained of ~7 s may not be very useful in earthquake engineering or in design codes, because there are basically no standard buildings that have that level of natural period [18]; however, newer isolated structures can have their periods in that range [19]; therefore, a first application of the main result is in seismic base isolation. As matter of fact, we finish this paper by highlighting that this one or single seismic predominant frequency has been validated by other means, or applied to solve a structural engineering problem: a successful structural control of isolated buildings through tuned mass damper [8] which is a device particularly sensitive to input frequency; that is, the passive control proposed was successful because near-field ground displacement does have one predominant frequency, at 0.13 Hz as assumed in that work due to the results available last year [5]. The present results suggest an adjustment and improvement towards 0.15 Hz, or 0.18 if liquefaction is considered; we talk about improvement because the results are based on a more robust and reliable method, as explained.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It can also be argued that the predominant period obtained of ~7 s may not be very useful in earthquake engineering or in design codes, because there are basically no standard buildings that have that level of natural period [18]; however, newer isolated structures can have their periods in that range [19]; therefore, a first application of the main result is in seismic base isolation. As matter of fact, we finish this paper by highlighting that this one or single seismic predominant frequency has been validated by other means, or applied to solve a structural engineering problem: a successful structural control of isolated buildings through tuned mass damper [8] which is a device particularly sensitive to input frequency; that is, the passive control proposed was successful because near-field ground displacement does have one predominant frequency, at 0.13 Hz as assumed in that work due to the results available last year [5]. The present results suggest an adjustment and improvement towards 0.15 Hz, or 0.18 if liquefaction is considered; we talk about improvement because the results are based on a more robust and reliable method, as explained.…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, by Fourier analysis of the ground displacement record, a more reasonable dispersion has been found at predominant frequencies [5,6]. In fact, the results have been considered "highly narrowbanded" and, based on this characteristic, a successful optimization of isolated structures with tuned mass dampers (TMD) has been possible, considering that TMD is very sensitive to the input frequency [8]. Those previous results were obtained by directly obtaining the power spectral density (PSD) of real seismic displacement records [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The differential evolution algorithm is often used to search for the optimal solution of nonlinear and nondifferentiable problems and has the advantage of fast convergence and high robustness (Price et al, 2005). Here, the differential evolution algorithm is used to optimize the parameters of the LVA and NES.…”
Section: Ordermentioning
confidence: 99%
“…Applying vibration absorbers is an effective means of vibration mitigation. Traditional vibration absorbers, namely, linear vibration absorbers (LVAs) (Yang et al, 2021), are widely used in the vibration mitigation of various systems, like curved beams (Yang et al, 2014) and isolated buildings (Morales, 2021). The LVA is a simple mass-damper-spring structure, but it can only mitigate vibration in a narrow frequency band and may generate new resonance peaks.…”
Section: Introductionmentioning
confidence: 99%
“…They have concluded that the hybrid vibration control system with the BIS and the distributed multiple TMDs is most beneficial, especially for tall buildings. Lately, Morales [55] has proposed a novel procedure for obtaining the optimum TMD design to reduce the bearing displacements of base-isolated structures. Apart from these passive TMD-based hybrid vibration control systems, recently researchers have presented an optimal design and performance of tuned inerter damper and TMD inerter devices installed in base-isolated structures, subjected to seismic excitations [56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%